PENERAPAN LEAN SIX SIGMA PADA UPAYA PENINGKATAN KUALITAS DAN EFISIENSI PROSES PADA PRODUKSI EMBOSSED SIGNAGE - Putra, Yohanes Widhiasmara; Kristina, Helena Juliana; Saryatmo, M Agung (Universitas Tarumanagara, 2024)
The research was conducted at an advertising company with the object of research being signage or advertisements with the purpose to improving the quality of production process, and increasing the efficiency value of the production process. Based on the results of field studies, waste occurs in the production process in the form of defects, overproduction and inventory waste. Data collection was carried out by direct observation at the company, and interviews with the operational director. It was found that the average percentage of embossed signage defects in January to June 2023 was 6%. The method used to overcome this problem is Lean Six Sigma with the DMAIC stages (Define, Measure, Analyze, Improve, Control). The define stage uses SIPOC and CTQ diagrams to identify problems. The measure stage will use WAM to identify waste. The PCE value obtained at the measure stage was 56.01%, and the DPMO and sigma values were 22,742 and 3.5. Next, an analysis of the causes of the problem is carried out at the analyze stage. The analysis was carried out with the help of tools in the form of fishbone diagrams, why-why analysis, and FMEA. In FVSM, PCE was found to be 58.26%, which indicates that there has been an increase in the efficiency of the production process. Based on the results of the analysis, suggestions for improvements are provided to improve the quality of production and production processes at the company. At the control stage, control is carried out on the results of proposed improvements strictly before recalculation is carried out after implementing the improvements.